Ninjurin1 Plays a Crucial Role in Pulmonary Fibrosis by Promoting Interaction between Macrophages and Alveolar Epithelial Cells. Issue 1 (December 2018) - Choi, Seungho; Woo, Jong; Jang, Yeong-Su; Kang, Ju-Hee; Hwang, Jong-Ik; Seong, Je; Yoon, Yeo; Oh, Seung
Abstract The transmembrane nerve injury-induced protein 1 (Ninjurin1 or Ninj1) is involved in progressing inflammatory diseases. In this study, we aimed to investigate a novel function of Ninj1 in pulmonary fibrosis. We found that the expression of Ninj1 in a patient cohort was upregulated in the lung specimens of idiopathic pulmonary fibrosis patients as well as mice with bleomycin-induced pulmonary fibrosis. In addition, the BLM-injected Ninj1 KO mice exhibited a mild fibrotic phenotype, as compared to WT mice. Therefore, we hypothesized that Ninj1 would play an important role in the development of pulmonary fibrosis. We discovered that Ninj1 expression increased in BLM-treated macrophages and alveolar epithelial cells (AECs). Interestingly, macrophages bound to BLM-treated AECs were activated. However, when Ninj1 expression was suppressed in either of AECs or macrophages, contact-dependent activation of macrophages with AECs was diminished. In addition, introduction of recombinant mouse Ninj11–50 to macrophages triggered an inflammatory response, but did not stimulate Ninj1-deficient macrophages. In conclusion, we propose that Ninj1 may contribute to activation of macrophages by enhancing interaction with AECs having elevated Ninj1 expression due to injury-inducing stimuli. Consequently, Ninj1 may be involved in the development of pulmonary fibrosis by enhancing inflammatory response of macrophages.